The The Effect Of Regional Original Revenue, General Allocation Funds, And Special Allocation Funds On Regional Expenditure In Regencies/Cities Of Central Java 2017-2020 - Mutiara, Arba; Ramadhanti, Fitria; Nur Rahma, Galuh (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2025)
This study aims to evaluate the extent to which Local Own Revenue (PAD), General Allocation Funds (DAU), and Special Allocation Funds (DAK) affect regional spending in regencies/cities in Central Java Province during the period from 2017 to 2020. The data used is sourced from secondary data obtained through publications from the Directorate General of Financial Equalization and the Central Bureau of Statistics during that period. The variables analyzed include PAD, DAU, DAK, and regional spending. This study uses panel data analyzed with multiple linear regression. Based on the analysis results, the most suitable model in this research is the Common Effect Model (CEM). The findings indicate that PAD and DAU have a significant impact on regional spending, while DAK does not show a significant effect. Collectively, the three variables (PAD, DAU, and DAK) have been proven to have a significant effect on local government spending in the regencies/cities of Central Java from 2017 to 2020. Keywords: Regional Original Revenue, General Allocation Fund, Special Allocation Fund, regional spending